2021
DOI: 10.3390/en14030716
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Natural Convection Heat Transfer Coefficient in Phase Change Material (PCM) Based Fin-and-Tube Heat Exchanger

Abstract: Latent heat thermal energy storage systems allow storing large amounts of energy in relatively small volumes. Phase change materials (PCMs) are used as a latent heat storage medium. However, low thermal conductivity of most PCMs results in long melting (charging) and solidification (discharging) processes. This study focuses on the PCM melting process in a fin-and-tube type copper heat exchanger. The aim of this study is to define analytically natural convection heat transfer coefficient and compare the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Shell-and-tube LHTES 11 usually offer high energy density, but they are lacking in heat transfer rate. Therefore, various types of LHTESs with fins protruding to the PCM have been designed 14 18 . Fins can increase the heat transfer rate significantly, but they are usually complicated to attach to the pipes reliably, which makes them expensive 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shell-and-tube LHTES 11 usually offer high energy density, but they are lacking in heat transfer rate. Therefore, various types of LHTESs with fins protruding to the PCM have been designed 14 18 . Fins can increase the heat transfer rate significantly, but they are usually complicated to attach to the pipes reliably, which makes them expensive 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Shell-and-tube LHTES 11 usually offer high energy density, but they are lacking in heat transfer rate. Therefore, various types of LHTESs with fins protruding to the PCM have been designed [14][15][16][17][18] . Fins can increase the heat transfer rate…”
mentioning
confidence: 99%
“…In the cylinder mode [47], which is considered as the ideal shell-tube configuration, the HTF flows inside the pipes, and the PCM is surrounded by the shell. Pakalka et al [48] experimentally and theoretically studied the natural convection heat transfer in the PCM-based fin and tube thermal exchanger. They found that the convection heat transfer coefficient was equal to 61 and 68 W/m 2 K in the experimental and theoretical methods, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The cylinder form considers as the best shell-tube design [42], in which the HTF flows in the channel surrounded by the PCM. Pakalka et al [43] investigated the thermal free convection in the fins combined heat exchanger. They stated that the thermal convection coefficient significantly improves in both experimental and theoretical procedures.…”
Section: Introductionmentioning
confidence: 99%